2016
DOI: 10.18240/ijo.2016.03.15
|View full text |Cite
|
Sign up to set email alerts
|

Elevated urine formaldehyde in elderly patients with primary open angle glaucoma

Abstract: Endogenous FA level is positively correlated with the neuronal defects of POAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Urinary 8-hydroxy-2′-deoxyguanosine (8-OHdG), a marker of oxidative DNA damage, has been reported to be significantly increased in patients with progressive normal tension glaucoma, compared to patients with non-progressive normal tension glaucoma [47]. Another study showed elevated urine formaldehyde in elderly patients with primary open angle glaucoma, compared to healthy controls [48]. However, in addition to a lack of contact with the eye, measurement of target molecules in urine can be confounded by the effects of filtration and reabsorption in the kidney.…”
Section: Molecular Biomarkers To Monitor Neurodegeneration In Glaucomamentioning
confidence: 99%
“…Urinary 8-hydroxy-2′-deoxyguanosine (8-OHdG), a marker of oxidative DNA damage, has been reported to be significantly increased in patients with progressive normal tension glaucoma, compared to patients with non-progressive normal tension glaucoma [47]. Another study showed elevated urine formaldehyde in elderly patients with primary open angle glaucoma, compared to healthy controls [48]. However, in addition to a lack of contact with the eye, measurement of target molecules in urine can be confounded by the effects of filtration and reabsorption in the kidney.…”
Section: Molecular Biomarkers To Monitor Neurodegeneration In Glaucomamentioning
confidence: 99%
“…Recent studies have highlighted the possible involvement of formaldehyde in a number of age-associated phenomena, dementia, depression and diabetes (type-2). Papers by Li et al [ 1 , 2 ], Cui et al [ 3 ], Tong et al [ 4 , 5 ] and Mei et al [ 6 ] have shown an association between formaldehyde and age-related dysfunction such as glaucoma, stroke, Alzheimer’s disease and memory decline. Furthermore, Tulpule and colleagues [ 7 , 8 ] have demonstrated that formaldehyde strongly stimulates glycolytic flux in astrocytes and neurones, implying its contribution to metabolic age-related dysfunction, (e.g.…”
mentioning
confidence: 99%